2000
DOI: 10.1046/j.1471-4159.2000.0752574.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Synthetase and Glutamine Synthetase‐Like Protein from Human Brain

Abstract: Glutamine synthetase (GS; EC 6.3.1.2), a key enzyme of glutamate metabolism, and another enzyme possessing high hydroxylamine-L-glutamine transferase activity comparable to that of GS and termed GS-like protein (GSLP) were purified from human brain concurrently. In two-dimensional electrophoresis, GS subunits migrate to at least six different positions (44 Ϯ 1 kDa, pI ϭ 6.4 -6.7), whereas GSLP subunits migrate to at least four different positions (54 Ϯ 1 kDa, pI ϭ 5.9 -6.2). Dependences of enzymatic activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…These data complement our previous results on altered level of GME and CK BB in cytoplasm fraction of PFC tissue [23,29]. Since the new extraction method used in present study takes into account particulate isoforms, such as GDH III and partially GSLP [41,42] in addition to cytoplasm isoforms, we are confident that we have measured total amounts of target proteins in the brain tissue. Unlike our previous experiments with cytoplasm fraction of PFC [23,29,37], in the current study we did not observe any difference in the level of total CK BB, GSLP, or GDH III between control and SCH groups in this brain region (and in CN or cerebellum as well).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These data complement our previous results on altered level of GME and CK BB in cytoplasm fraction of PFC tissue [23,29]. Since the new extraction method used in present study takes into account particulate isoforms, such as GDH III and partially GSLP [41,42] in addition to cytoplasm isoforms, we are confident that we have measured total amounts of target proteins in the brain tissue. Unlike our previous experiments with cytoplasm fraction of PFC [23,29,37], in the current study we did not observe any difference in the level of total CK BB, GSLP, or GDH III between control and SCH groups in this brain region (and in CN or cerebellum as well).…”
Section: Discussionsupporting
confidence: 90%
“…4673-5007, Clone No. 49G3, Biogenesis, UK) at 1:1,000,000 working dilution; the amount of GSLP immunoreactive protein and the levels of GDH isoforms (readily soluble GDH I + II and associated with particulate fraction GDH III) were evaluated in brain extracts using specific rabbit antisera raised in the Laboratory of Neurochemistry MHRC RAMS and described earlier [41,42], each at 1:10,000 working dilution;…”
Section: Internal Standardmentioning
confidence: 99%
See 1 more Smart Citation
“…A proteomic study by Prabakaran et al also described reduced glutamine synthetase in schizophrenia in area 9 of the frontal cortex (Prabakaran et al, 2004). Consistent with reports of multiple isoforms of glutamine synthetase (Chakrabarti et al, 1995;Boksha et al, 2000), the study by Burbaeva et al also showed that protein expression of an enzyme similar in activity and immunoreactivity to glutamine synthetase, termed glutamine synthetase like protein (GSLP), was increased in this brain region. In addition to protein levels, this study measured the transferase activity of glutamine synthetase and GSLP; however, no changes were detected.…”
Section: Expression Of Glutamine Synthetase In Schizophreniamentioning
confidence: 57%
“…Brain glutamine synthase enzymatic activity was routinely measured as previously described (Boksha et al, 2000) by the transferase reaction (ADP+L-Gln+NH2OH) and was determined by measuring -glutamyl hydroxamate formation. Cells were treated with cyclic adenosine monophosphate (Sigma Aldrich, 100 mM, 3 h) and subsequently with glutamate (Sigma Aldrich, 1 mM, 1 h).…”
Section: Glutamine Synthetase Activitymentioning
confidence: 99%